2010
DOI: 10.26719/2010.16.2.180
|View full text |Cite
|
Sign up to set email alerts
|

Complementary feeding patterns in a developing country: a cross-sectional study across Lebanon

Abstract: This first, large-scale study on complementary feeding in Lebanon analysed the timing and types of food introduced to infants according to mothers' demographic and socioeconomic and infants' characteristics. A cross-sectional survey over 10 months found that the majority of infants were introduced to solid foods at or after 4 months of age. A large number of infants were given liquids other than breast or formula milk earlier. Women in employment outside the home were almost twice as likely to introduce solid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
32
4
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 1 publication
12
32
4
1
Order By: Relevance
“…This finding is similar to findings from other developing countries demonstrating the low adherence to the WHO breastfeeding guidelines [26,27]. In Lebanon, past research has cited detrimental cultural beliefs (insufficient milk, “bad” colostrum) [19], unfavorable hospital policies [20] and discouraging physician advice as potential barriers to exclusive breastfeeding and catalysts to breastfeeding cessation.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This finding is similar to findings from other developing countries demonstrating the low adherence to the WHO breastfeeding guidelines [26,27]. In Lebanon, past research has cited detrimental cultural beliefs (insufficient milk, “bad” colostrum) [19], unfavorable hospital policies [20] and discouraging physician advice as potential barriers to exclusive breastfeeding and catalysts to breastfeeding cessation.…”
Section: Discussionsupporting
confidence: 85%
“…In the same survey, only 18% of mothers breastfed within 30 minutes after delivery. Hospital policies, employment and type of delivery have all been shown to significantly affect breastfeeding practices in Lebanon [18,19]. One study showed a significant effect of religion and pediatrician gender on breastfeeding [16] while another documented common cultural beliefs that may discourage breastfeeding [20].…”
Section: Introductionmentioning
confidence: 99%
“…Rice has been a principle complementary feeding in other parts of Iran (9) and Middle East countries such as Iraq (15). Still, about half of mothers in this study were not giving feeds in the appropriate type similar to findings of the study by Batal et al, in Lebanon that indicates to need to interventions (7,14).…”
Section: Complementary Feeding Practices and Related Factorssupporting
confidence: 74%
“…This finding is much less compared with the report by Batal et al, in Lebanon that found only 11.9% of mothers practiced complementary feeding at appropriate time (7). This difference might be due to variations in the population with different cultures under study.…”
Section: Complementary Feeding Practices and Related Factorscontrasting
confidence: 55%
See 1 more Smart Citation